Antibacterial Effectiveness of White Champaca Flower (Michelia alba dc) Against Growth of Corynebacterium diphtheriae - Putri, Tiara Nandita; Budianto, Nugroho Eko Wirawan; Tjandra, Lusiani (Universitas Wijaya Kusuma Surabaya, 2025)
Background: Corynebacterium diphtheriae is a bacterium that attacks the respiratory tract, especially the larynx, tonsils, and throat. These bacteria can release toxins that can cause diphtheria. One of the nutritious plants that people often use is the white Champaca flower, or Michelia alba. Objective: This study aimed to examine the antibacterial effectiveness of white champaca flower (Michelia alba dc) against the growth of Corynebacterium diphtheriae. Methods: Experimental research method with post-test only control group design using Cup-plate technique of ethanol extract of white Champaca flower (Micheia alba) in various concentrations (20%, 40%, 60%, 80%, and 100%) and Erythromycin as a positive control and aquades as a negative control. Results: The results of this research are that the minimum inhibitory concentration against the growth of Corynebacterium diphtheriae bacteria at a 20% concentration is 42.16 mm, the concentration of 40% is 47.21 mm, the concentration of 60% is 51.66mm, while at the concentration of 80% the average diameter of the inhibitory zone is 54.49 mm and also at the concentration of 100% the average diameter of the inhibition zone is 54.69 mm which is the average diameter of the largest inhibition zone. The negative control with an inhibitory zone diameter of 0 mm, while the positive control with an inhibitory zone diameter of 44.21 mm. Conclusion: White Champaca flower extract (Michelia alba dc) had antibacterial effectiveness against the growth of Corynebacterium diphtheriae and at a concentration of 100% it is the most effective concentration in inhibiting the growth of Corynebacterium diphtheriae bacteria.